HUBUNGAN PENGETAHUAN DAN SIKAP PETUGAS LABORATORIUM PATOLOGI KLINIK TERHADAP PENERAPAN STANDARD OPERATING PROCEDURE (SOP) PENANGANAN BAHAN INFEKSIUS DI RSUD ARIFIN ACHMAD PROVINSI RIAU - Rizkika, Suci; Restuastuti, Tuti; ", Fatmawati (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Each laboratory officers who handle blood or human body fluids potentially infected, the risk of exposure or getting injury. Therefore, in the implementation of laboratory services are always required SOP as a handle for the officer to reduce the occurrence of infectious diseases. Standard operating procedure is a method written as fundamental guidance to prevent the risks of infection for laboratory officers. This research aimed to determine correlation between knowledges and attitudes of RSUD Arifin Achmad Riau Province clinical pathology laboratory officers toward Standard Operating Procedure (SOP) implementation of Infectious material management. This is an analityc survey study with cross-sectional method. Samples obatained by total sampling method based on inclusion criteria as many as 34 laboratory officers.This research showed 17 people (50%) have sufficient knowledge, 18 people (52.9%) have a negative attitude and 25 people (73.5%) implements SOP. Data processed by using Chi-Square test has been found that there was no significant relationship between knowledge and attitudes on clinical pathology laboratory officers toward Standard operating procedure (SOP) implementation of infectious material management in RSUD Arifin Achmad Riau Province.Keyword : Standard Operating Procedure (SOP) implementation of infectious material management, knowledges and attitudes.